Efficiency of Organic Lip Balm Containing Strawberry, Honey and Peppermint - Sazeli, Zul Afiq; Subramaniam, Sanggary; Subahar, Sharveena; Wong Zhi Yan,; Norain Ahmad Nordin, (Multidisciplinary Applied Research and Innovation, 2021)
Among all cosmetic products, lip balm formulations are most widely used to enhance the beauty of lips and add glamour touch to the makeup. This work involves the development of a lip balm formulated with certified organic raw materials and the execution of tests including evaluation of organoleptic characteristics and satisfaction of cosumer. The three product was produce with three basic ingredient and one additional ingredient like strawberry, honey and papermint and this three product will be test on the water seal test, high temperature test and the consumer satisfaction. The result shows that from this three product, strawberry lip balm is the most preferred lip balm but it will take the shortest time to melting. In general, the amount of each ingredient was stabilized in order to achieve a resistance to temperature variations, pleasant flavour, and smoothness during application, adherence and easy intentional removal.